Материалистическая диалектика. Законы и категории - Митин М. Б. Марк Борисович; Шептулин А. П. Александр Петрович; Юсупов Э. Ю.; Хайруллаев М. М.; Органова О. Н.; Малькова Т. П. (Ташкент, Фан, 1982)
Авт. указаны на 3-й с.